2016
DOI: 10.1089/ham.2016.0032
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypobaric Hypoxia Induces Right Ventricular Hypertrophy and Apoptosis in Rats: Therapeutic Potential of Nanocurcumin in Improving Adaptation

Abstract: Nehra, Sarita, Varun Bhardwaj, Santosh Kar, and Deepika Saraswat. Chronic hypobaric hypoxia induces right ventricular hypertrophy and apoptosis in rats: therapeutic potential of nanocurcumin in improving adaptation. High Alt Med Biol. 17:342-352, 2016.-a sustained work load on the right heart on ascent to high altitudes promotes right ventricular hypertrophy (RVH), which eventually undergoes decompensation and promotes pathological damage. However, the exact set of events leading to damage remains unidentified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
1
15
0
2
Order By: Relevance
“…Several studies have described that in different PH models, the inflammatory molecule IL-6 is increased both in plasma and RV tissue, which could be involved in cardiac function and morphology [36]. This is supported by a study by Nehra et al [14] in rats with RVH induced by hypobaric hypoxia (7620 m) showing an increase in circulating levels of TNF-α and IL-6, and these molecules were associated with a decompensated transition to RHF. Moreover, a recent study in mice with transverse aortic constriction shows new insight into hypoxia-induced mitogenic factor (HIMF), a cytokine-like protein that could induce cardiac hypertrophy, fibrosis and myofibroblast differentiation through IL-6 [97], which results in an interesting pathway to be analyzed in the transition to HF under this particular condition.…”
Section: Inflammationmentioning
confidence: 75%
See 1 more Smart Citation
“…Several studies have described that in different PH models, the inflammatory molecule IL-6 is increased both in plasma and RV tissue, which could be involved in cardiac function and morphology [36]. This is supported by a study by Nehra et al [14] in rats with RVH induced by hypobaric hypoxia (7620 m) showing an increase in circulating levels of TNF-α and IL-6, and these molecules were associated with a decompensated transition to RHF. Moreover, a recent study in mice with transverse aortic constriction shows new insight into hypoxia-induced mitogenic factor (HIMF), a cytokine-like protein that could induce cardiac hypertrophy, fibrosis and myofibroblast differentiation through IL-6 [97], which results in an interesting pathway to be analyzed in the transition to HF under this particular condition.…”
Section: Inflammationmentioning
confidence: 75%
“…Additionally, the activation of molecular pathways and morphological changes, such as uncoupled endothelial nitric oxide synthase (eNOS), pro-inflammatory cytokines such as interleukin 1 and 6 (IL-1 and IL-6), and oxidative stress, among others, lead to pulmonary arterial remodeling and ultimately definitive pulmonary hypertension (PH) [11,12]. Thus, the principal consequence of HAPH is pressure overload (PO)-induced right ventricular hypertrophy (RVH) in the long term [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The rat model of chronic hypoxia employed in this study is a reversible model of RV hypertrophy that occurs prior to decompensated RV failure (Nehra, Bhardwaj, Kar, & Saraswat, ). Thus, our findings reflect what is observed in the nonfailing RV.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometry analysis of right ventricular hypertrophy (RVH) was performed by analyzing Fulton’s index (RV/LV+S and RV/BW) and histopathological assessment via Masson’s trichrome staining as previously described. 22 Circulating levels of atrial natriuretic factor (ANF) (ab108797, Abcam, Cambridge, UK) and brain natriuretic peptide (BNP) (ab108816, Abcam) were estimated as markers of cardiac hypertrophy using commercially available ELISA kits; the assays were performed according to manufacturer’s instructions. Tissue distribution of ANF was examined as a marker of hypertrophy by immunohistochemistry, and changes in tissue-architecture were analyzed by immunofluorescence staining using α-actin/DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, we have previously shown that nanotized curcumin (NC) ameliorates hypoxia stress both in vitro and in vivo. 3 , 4 , 22 , 23 Hypoxic stress elicits multiple physiological damages on normal physiological functions. 24 Additionally, the normal functioning of cardiomyocytes critically relies upon an optimal oxygen supply.…”
Section: Introductionmentioning
confidence: 99%